EFFECT OF WEED MANAGEMENT ON WEEDS, GROWTH AND YIELD OF SUMMER GREENGRAM ( YIELD OF SUMMER GREENGRAM (VIGNA RADIATA L.) - CHAUDHARI; DESAI, V. D; CHAUDHARI, L. J; P. R, S. N.; CHAUDHARI, (The Bioscan, 2016)
A field experiment was conducted at College farm, Navsari Agricultural University, Navsari (Gujarat) during summer season of the year 2014 to study the “Weed management study in summer green gram (Vigna radiata L.) under south Gujarat condition” Among the different herbicidal weed management treatments, Pendi methalin @ 1.0 kg ha-1 PE (T4) recorded lowest weed population of monocot, dicot and sedge at 25, 50 and at harvest of crop, which resulted in lowest dry weight of weed (435 kg ha-1), highest weed control efficiency (79.59 %) as well as lower weed index (7.55 %). Weed free treatment (T1) registered significantly higher number of branches per plant at harvest (8.88), yield and yield attributing characters viz., number of pods per plant-1(20.73) followed by T9 (8.85 and 20.40), T8 (8.79 and 19.73) and T4 (8.17 and 18.40), respectively. The significantly higher seeds and stover yield (1378 and 1627 kg ha-1, respectively) were recorded in weed free treatment. Effective weed control in green gram can be achieved by hand hoeing at 20 and 30 DAS during crop growth period with an alternative is application of pendi methalin 1.0 kg ha-1 PE.